Interband absorption and its relation to the electronic structure of Co-Cr solid solutions - Bondar, V.M.; Stashchuk, V.S.; Polianska, O.P.; Kudin, V.G.; Statsenko, A.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
The refraction n and absorption χ indices of paramagnetic Сo-Cr alloys with 10, 20 and 35% chromium concentrations were measured within the spectral range 0.23 to 2.8 µm (0.44…5.36 eV) at room temperature by spectral ellipsometric methods. Based on these data, the dielectric permittivity ε, optical conductivity σ and reflection coefficient R at normal incidence were calculated. The dispersion of optical conductivity σ(hν) and dispersion curves of residual optical conductivity σ(hν) = σ(hν) – (1 – c) σCo(hν) were analyzed in detail (c – Cr impurity concentration, σCo(hν) – optical conductivity of Co solvent). It has been ascertained that new impurity bands are formed in the electronic spectrum of Co solvent when Cr impurities are added, which are responsible for the extra absorption in Сo-Cr alloys. The localization of impurity energy levels in Co-Cr alloys at 1.8…2.0 eV above the Fermi level has been suggested.